2023
DOI: 10.5093/pi2022a15
|View full text |Cite
|
Sign up to set email alerts
|

Daily Heterosexist Experiences in LGBTQ+ Adults from Spain: Measurement, Prevalence, and Clinical Implications

Abstract: Lesbian, gay, bisexual, transgender, and queer (LGBTQ+) individuals face unique stressors related to their sexual and gender identities that have a detrimental impact on their mental health. Nonetheless, studies have not yet investigated these minority stressors among LGBTQ+ individuals from Spain. The limited availability of standardized tools/ instruments to measure minority stressors in Spanish makes it challenging to explore these experiences among Spanish speaking individuals. The present study aimed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 55 publications
(79 reference statements)
1
13
0
Order By: Relevance
“…Items were coded as present (1) (options 1–5) and absent (0) to calculate total scores (Balsam et al, 2013). Preliminary results on our sample indicated that the translated version of DHEQ has a good factor structures and predictive validity when associated with mental health outcomes (Ronzón-Tirado et al, 2023). Confirmatory factor analysis indicated a good fit for the six dimensions of the DHEQ scale (Ronzón-Tirado et al, 2023).…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Items were coded as present (1) (options 1–5) and absent (0) to calculate total scores (Balsam et al, 2013). Preliminary results on our sample indicated that the translated version of DHEQ has a good factor structures and predictive validity when associated with mental health outcomes (Ronzón-Tirado et al, 2023). Confirmatory factor analysis indicated a good fit for the six dimensions of the DHEQ scale (Ronzón-Tirado et al, 2023).…”
Section: Methodsmentioning
confidence: 90%
“…Preliminary results on our sample indicated that the translated version of DHEQ has a good factor structures and predictive validity when associated with mental health outcomes (Ronzón-Tirado et al, 2023). Confirmatory factor analysis indicated a good fit for the six dimensions of the DHEQ scale (Ronzón-Tirado et al, 2023). In this sample, acceptable internal consistency was found for each subscale (ranged α = .69–.80, 95% confidence interval [CI] = [0.63–0.75] to [0.75–0.84]) and total score (α = .91, 95% CI = [0.89–0.93]).…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…In general, these problems diminish in countries where there are public policies of inclusion and diversity for sexual minorities (Aivadyan et al, 2023). Although studies from different parts of the world have shown a higher prevalence of suicidal behaviour in sexual minorities compared to other populations (Pharr et al, 2022), it is worth noting that in Spain the exact rate of suicide in the LGBTQ + population is unknown (Ronzón-Tirado et al, 2023). Mortality registries collect age, sex, race, and other personal characteristics of the individual, but do not include information on sexual orientation or gender identity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that lesbian, gay, bisexual, transgender, queer, and asexual people (LGBTQA) experience discrimination, victimization, and stigmatization because of their gender and sexual identity, a primary source of minority stress [ 1 , 2 , 3 ]. According to the minority stress model [ 4 , 5 , 6 , 7 ], chronic minority stress leads to several somatic and psychiatric health issues in the minority population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%